Metabolic processes in pigs and their productivity depending on the microclimate of the premises - А. І. DMYTROTSA (Передгірне та гірське землеробство і тваринництво, 2021)
A number of domestic and foreign scientific studies conducted in recent years have shown that the parameters of the microclimate in the premises have a significant impact on the physiological state, the course of metabolic processes in the body and the productive qualities of animals. In animal husbandry, there are certain rules that state that the correct microclimate in the pigsty affects the appetite, health and development of piglets. It should also be noted that different sex-age and productive groups of pigs, and in particular such groups of pigs as pregnant and lactating sows, as well as newborn and weaned piglets, which are most sensitive to the smallest deviations, are particularly sensitive to the negative effects of indoor microclimate parameters. In addition, during the rearing of piglets, it is necessary to create optimal conditions for the most painless passage of stressful phenomena associated with birth, weaning from the sow, change of location, the creation of new hierarchical relationships in the group. For this, innovative technologies are being developed to ensure comfortable microclimate conditions in pig housing at different times of the year.